Reconocimiento histórico cultural de la vereda el Tambillo (Rivera – Huila) (2022)
The department of Huila is in a historical context, where the cultural and natural variety have generated a great impact on territorial development, starting from the tourism of its municipalities that, in one way or another, are linked to the ancestral dynamics of our ancestors. Rivera Huila is one of the representative municipa lities of local tourism, it is in constant development due to its strategic environmental location and the ancestral wealth which is immersed in rural areas. The village of El Tambillo, located in the municipality of Rivera and belonging to the eastern mou ntain range, has generated an ancestral mystery due to the remains found apparently descendants of the Andaquies and Tamas, tribes that roamed these high areas and that inhabited, at the time, which is currently known as El Tambillo. Said archaeological fi nds, such as work tools, artisanal objects and engraved rocks (petroglyphs), have remained in the hands of the residents and illegal looters, who, without having any knowledge and heritage value, generate alterations on the vestiges, in order to to highlig attention of tourists who currently visit the village frequently.